Prediction the AC Breakdown Voltage in Point/Plane Air Gaps with Barrier Using Design of Experiments - Abdelghani Rouini; Djillali Mahi; Tahar Seghier (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Breakdown voltage characteristics of air gaps considered a random process we have investigated how to find relevant statistical different leading to breakdown or with standing during an impulse voltage test under the same condition for a plane high voltage electrode and a grounded electrode configuration.In the present paper methods of the modelling and prediction of the AC breakdown voltage  in point-plane air gaps are investigated. An analysis based on experiments design method has been developed with indicates that.Measurements to contain some relevant information test at early stages in reduced time frame investigation were done on a point-plane with barrier varying in position and size. The barrier used was mounted vertically between the electrodes.The use of methodology of experiments design is one of this methods and present an original idea in high voltage prediction problems several factors were considered,namely the distance between electrodes and different parameters of the barrier such us is dimension and his holes.The experimental results are compared with results from numerical simulations.We firstly present the principals of this model then we apply it to the study of barrier effect. A good agreement has been found between the computed and experimental results.